Tech for Good: Leveraging AI and IoT for Climate-Resilient Economic Development (Proceeding of the International Conference on Economics, Accounting, and Taxation, 2025)
This study examines the role of smart technology, particularly Artificial Intelligence (AI) and the Internet of Things (IoT), in strengthening economic resilience in the face of climate change impacts. Using a qualitative descriptive approach with a literature stufy method, secondary data was obtained from scientific journals, books, proceedings, and relevant online articles. The analysis was conducted through reduction, categorization, and thematic analysis of the relevant literature. The results show that AI contributes significantly to improving economic efficiency and risk prediction compabilities. While IoT strengthens connectivity and automation that support supply chain stability, the intregration of AI and IoT in the agricultural sector significantly increases productivity and food security. In addition, smart technology is also an effective mitigation tool against exctreme climate variations that impact the economy and society. This study emphasizes the importance of cross-sector collaboration and digital infrastructure investment to build adaptive and sustainable economic resilience. The implication of this research provide a basis for policy strategies and digital innovation in an era of increasing dynamic climate change.